Analisis Pengaruh Pendidikan, Kesehatan dan Upah Terhadap Produktivitas Tenaga Kerja di Provinsi Jawa Tengah - Puspasari, Dwi (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2020)
Labor productivity is a describes of the capability of the worker in the resulting output. The higher of output produced by a worker, showed the higher of Â worker productivity levels. The quality of labor will affect the productivity of the output produced. Labor productivity in Province of Central Java is lower when compared with other provinces on the island of java. This research aims to analyze the impact of variable education, health and wage on labor productivity in Centra Java year of 2010-2015. The analytical method use in this study is panel data regression. The analytical method of this research is Fixed Effect Model (FEM).The result is variable education, health and wage is significant andÂ  has positive impact on labor producticity.